Let $F$ be a finite field and $i$ an integer. Calculate the sum of all the elements of $F$, each raised to the $i$th power.

My approach so far:

Let $F=(0,1,\alpha,\alpha^2,...,\alpha^{p^n-1})$, where $p$ is a prime number and let $\sigma=1+\sum_{k=1}^{p^n-1}(α^k)^i$ be the desired sum.

Since $F$ is a ring, each element has an additive inverse. Thus, the trivial case of $i=1$ results in $\sigma=1+[\alpha+(-\alpha)+\alpha^2+(-\alpha^2)+\cdots+\alpha^{p^n-1}+(-\alpha^{p^n-1})]=1$.

We can also calculate the trivial case of $i=0$, where $\sigma=1+p^n-1=p^n$

In the general case, let $i=t (\text{mod } p^n)$.
Then: $i=t+mp^n$, where $t,m$ are integers. We take into account the fact that the order of the multiplicative group of the finite field is $p^n$, so each element raised to the $p^n$ equals $1$. Thus $σ=1+α^t+α^{2t}+\cdots+α^{t(p^n-1)}$. This is the sum of a geometric progression, plus $1$. Thus, $σ=1+α(α^{p^n-1})/α-1$ = $ 1$+($α^{p^n}-α$)/${\alpha-1}$. But according to Lagrange's theorem, for every $\alpha\in F$, the polynomial $x^{p^n}-x$ is zero. It follows that $\sigma=1$.

An important question is raised: Is it true that the characteristic of the finite field is $p$ if its order is $p^n$? If so, the case for $i=0$ leads to $σ=0≠1$ and all cases have been considered?

  • 1
    $\begingroup$ The order of the multiplicative group of a finite field $F$ with $p^n$ elements is $p^n-1$. In this case, the characteristic of $F$ is indeed $p$. Also, your case $i=1$ has too many summands, but the idea is right. $\endgroup$ – Thomas Poguntke May 5 '15 at 16:07
  • 2
    $\begingroup$ $\alpha^{p^n-1}=1$, so your sum has that term twice. The largest distinct power of a primitive element you have is $\alpha^{p^n-2}$. So your sum contains $1^i$ twice, and the sum is off by one. Similarly, you should look at the congruence $i\equiv t\pmod{p^n-1}$. $\endgroup$ – Jyrki Lahtonen May 5 '15 at 16:08
  • 2
    $\begingroup$ If $\text{char } F \neq 2$, each nonzero element has an additive inverse, so for $i = 1$, $\sigma = 0$. $\endgroup$ – Travis Willse May 5 '15 at 16:10

A different approach. Assume that $i$ is such that $\alpha^i\neq1$. Let $$ \sigma_i=\sum_{x\in\Bbb{F}_{p^n}}x^i $$ be the sum. We get that $$ \alpha^i\sigma_i=\alpha^i\left(\sum_{x\in\Bbb{F}_{p^n}}x^i\right) =\sum_{x\in\Bbb{F}_{p^n}}\alpha^ix^i= \sum_{x\in\Bbb{F}_{p^n}}(\alpha x)^i. $$ Here $\alpha x$ ranges over the field when $x$ does, so the last sum is just $\sigma_i$. Thus $$ \alpha^i\sigma_i=\sigma_i. $$ Given that $\alpha^i\neq1$ I trust you to make the final deductive step. :-)

The condition $\alpha^i\neq 1$ is satisfied, iff $i\not\equiv 0\pmod{p^n-1}$. If $i$ is a multiple of $p^n-1$ your sum consists of several terms equal to $1$, which is another easy case.

  • $\begingroup$ Certainly a much more compact and refined approach than mine! Thank you! $\endgroup$ – MathematicianByMistake May 5 '15 at 16:17

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.